CHARACTERISTICS OR STRATEGY? THE MODERATING ROLE OF MARKET KNOWLEDGE IN SHAPING SMES’ INTERNATIONAL MARKETING DECISIONS - Koeswandi, Tika; Gaffar, Vanessa; Wibowo, Lili; Andriana, Denny; Primaskara, Ery (Jurnal Riset Bisnis dan Manajemen, 2025)
In an increasingly globalized market, SMEs face distinct challenges in making effective international marketing decisions (IMD). This study explores how International Entrepreneurial Marketing Strategy (IEMS) and internal SME characteristics influence IMD, with market knowledge as a moderating variable. Based on a survey of 220 export-oriented SMEs in West Java, Indonesia, moderated regression analysis reveals that both SME characteristics and IEMS significantly affect IMD. However, market knowledge only strengthens the influence of IEMS on IMD, without moderating the effect of internal characteristics. These findings highlight the strategic value of market knowledge in enhancing entrepreneurial marketing effectiveness. Integrating internal capabilities with contextual insight enables SMEs to make informed, agile, and competitive decisions. The study offers valuable theoretical contributions and practical implications for policymakers and international marketing strategists in emerging market contexts.